A new species of Luehea (Malvaceae, Grewioideae) from the Brazilian Atlantic Forest - Samuele Gerace; Massimo G. Bovini; José Fernando A. Baumgratz (Acta Botânica Brasílica)
Abstract We describe here the new species Luehea peruzziana Gerace, Bovini & Baumgratz, endemic to the Brazilian Atlantic Forest, and restricted to the state of Espírito Santo, in the south-eastern region of the country. Morphological description, illustration with details of vegetative and reproductive structures, and comments on taxonomy, distribution, phenology, and conservation status are provided. Furthermore, given the morphological similarity with L. ochrophylla Mart., a comparative analysis between these two taxa is reported.